Genome-Resolved Metagenomics Extends the Environmental Distribution of the Verrucomicrobia Phylum to the Deep Terrestrial Subsurface - Sophie L. Nixon (American Society for Microbiology, 2019)
ABSTRACT Bacteria of the phylum Verrucomicrobia are prevalent and are particularly common in soil and freshwater environments. Their cosmopolitan distribution and reported capacity for polysaccharide degradation suggests members of Verrucomicrobia are important contributors to carbon cycling across Earth’s ecosystems. Despite their prevalence, the Verrucomicrobia are underrepresented in isolate collections and genome databases; consequently, their ecophysiological roles may not be fully realized. Here, we expand genomic sampling of the Verrucomicrobia phylum by describing a novel genus, “Candidatus Marcellius,” belonging to the order Opitutales. “Ca. Marcellius” was recovered from a shale-derived produced fluid metagenome collected 313 days after hydraulic fracturing, the deepest environment from which a member of the Verrucomicrobia has been recovered to date. We uncover genomic attributes that may explain the capacity of this organism to inhabit a shale gas well, including the potential for utilization of organic polymers common in hydraulic fracturing fluids, nitrogen fixation, adaptation to high salinities, and adaptive immunity via CRISPR-Cas. To illuminate the phylogenetic and environmental distribution of these metabolic and adaptive traits across the Verrucomicrobia phylum, we performed a comparative genomic analysis of 31 publicly available, nearly complete Verrucomicrobia genomes. Our genomic findings extend the environmental distribution of the Verrucomicrobia 2.3 kilometers into the terrestrial subsurface. Moreover, we reveal traits widely encoded across members of the Verrucomicrobia, including the capacity to degrade hemicellulose and to adapt to physical and biological environmental perturbations, thereby contributing to the expansive habitat range reported for this phylum. IMPORTANCE The Verrucomicrobia phylum of bacteria is widespread in many different ecosystems; however, its role in microbial communities remains poorly understood. Verrucomicrobia are often low-abundance community members, yet previous research suggests they play a major role in organic carbon degradation. While Verrucomicrobia remain poorly represented in culture collections, numerous genomes have been reconstructed from metagenomic data sets in recent years. The study of genomes from across the phylum allows for an extensive assessment of their potential ecosystem roles. The significance of this work is (i) the recovery of a novel genus of Verrucomicrobia from 2.3 km in the subsurface with the ability to withstand the extreme conditions that characterize this environment, and (ii) the most extensive assessment of ecophysiological traits encoded by Verrucomicrobia genomes to date. We show that members of this phylum are specialist organic polymer degraders that can withstand a wider range of environmental conditions than previously thought.